Thermal Ionization-Isotope Dilution Mass Spectrometry Determination of Ruthenium in Spent Nuclear Fuel - Jeon, Young-Shin; Park, Yang-Soon; Kim, Jung-Suk; Han, Sun-Ho; Joon Park, Yong (Asian Journal of Chemistry, 2013)
The optimum conditions for determining ruthenium in spent nuclear fuel were investigated by thermal ionization-isotope dilution mass spectrometry (TI-IDMS). Silica gel, boric acid and Ba(NO3)2 as an ionization enhancer and sucrose and HI solution as a reducing agent needed to be loaded with a sample on a rhenium filament. A single filament provided a large peak with increased stability and less isobaric effect than double filament. The filament current needed to be increased slowly to 5 A at a rate of 0.1 A/min to obtain good results. Distillation method was effective for separation of ruthenium from the isobaric elements in a sample solution. In this optimum analytical condition, ruthenium concentration of 1,570 μg/g was obtained from the spent nuclear fuel (average burn-up of 57,000 MWd/tU) sample.